PELAYANAN SURAT IZIN MENGEMUDI DI KEPOLISIAN RESORT KOTA PONTIANAK - Rahmat Purbadi E.21110105 (FISIP Universitas Tanjungpura, 2013)
The problem in this research is the creation of service Driving License (SIM) which is conducted by the police officers are not in accordance with the wishes of the people. Besides, the attitude of staff in providing services can not maintain a working relationship and to create satisfaction to the people it serves, such as time in service efficiency, ease of service, and the justice ministry. Furthermore, the difference in the services provided by police officers, it's based on the size of the consideration provided by the community. The results showed that the public is often complained of the length of time obtaining a driving license because there are several steps that must be taken by the applicant, particularly in the manufacture of the new SIM. Where in the process and procedures the applicant must pass the theory test, and then have to pass the driving test through simulation. Furthermore the attitude of the police in providing services Driving License (SIM) in Pontianak Police alacrity shown by service personnel in providing services and a sense of responsibility towards tenggung the job done. From the results of the study found that police officers have a sense of responsibility. It can be seen from the evidence that the officer had been trying to come to work in accordance with the working hours specified by the Indonesian National Police Repoblik in performing their duties. Further transparency in service cost driving license (SIM) in Pontianak Police are principles that guarantee freedom of access or for any person to obtain information about the cost of driver's license, information on rates, the process of making and issuing drivers' licenses, as well as the results achieved . Responding Polrestas phenomena are expected to: 1) Provide good service although not supervised parties / Provost, 2) Adding an employee at the registration primarily to provide services to the community that the applicant has a low HR, 3) Adding facilities and streamline operations computer programs on line until the final stage of registration pelayananpembuatan SIM, not only limited to the production process alone, 4) Provide health tests and practice tests in an environment where institutions, and 5) Supervise and implement the sanctions, if any local officials who violate the rules, such as taking bribesKeywords: Effectiveness,Service, Driving License (SIM)